Understanding the Present Situation of Drought and the Areas Affected By It with Special Reference to Andhra Pradesh: Examining the impacts of drought on agricultural productivity in Andhra Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2018)
An inadequacy in rainfall causes exhaustion of soil moisture, fall in surface and ground water levels which thusly is probably going to deleteriously affect horticultural tasks, because of lacking accessibility of water for the crops, particularly amid the basic phases of plant development. The correlation between quantum of rainfall and the trigger for drought in India fluctuate crosswise over agro-climatic zones. Drought is a climatic hazard and a noteworthy danger among the common climatic hazards to vocation and financial development of people. Drought might be characterized as the scanty accessibility of water coming about because of subnormal or erratic rainfall distribution, or a blend of the two variables for an extensive stretch. In any case, it affects a wide district for a season or for back to back years. The arid zones are increasingly vulnerable to drought as their wellspring of rainfall relies upon few rainfall occasions. The primary goal of this examination is to contemplate on climate, rainfall and drought status in Andhra Pradesh. The state spread over with two particular geographical districts, Rayalaseema and Coastal Andhra. Andhra Pradesh is a critical State in Nation's Food Production. as of late, drought and other regular disasters have unfavourably affected the State's economy and its people. Agriculture keeps on being monsoon dependant, fundamentally on South West Monsoon (SWM) through which State gets 23 of its rainfall. The State with 5 constantly drought inclined districts (viz., Anantapur, Kadapa, Chittoor, Kurnool, and Prakasam) out of 13 districts.